Time-Temperature Curve Definition According to Fuel Type - Milan Dj. Blagojevich (Communications - Scientific letters of the University of Zilina, 2006)
An idealized temperature curve of compartment fire has three, distinct phases: growth phase - development phase from ignition to flashover, steady-burning phase, and decay phase. The experimental results performed in recent years show that the standard temperature curve proposed by the International Standards Organization (ISO) as well as ASTM E119 time-temperature curve selected for a standard fire resistance test do not satisfactorily describe fire phases for different fuel types. In this paper we propose the definition of the time-temperature curve by means of a unique function in which the fuel type is defined with parameters.